COMPLETE ORAL REHABILITATION WITH HYBRID PROSTHESIS. CASE REPORT - Elena Luca; Cristina Iordache; Cornelia Brezulianu; Anca Mihaela Vițalariu; Antonela Beldiman (Romanian Society of Oral Rehabilitation, 2019)
Aim of the study The aim of the study was to present a case report of a complex partially edentulous status treated with hybrid prosthesis, removable partial dentures with precision attachment. Material and methods A 47 year old female patient reported to dental clinic complaining of missing multiple teeth in the upper jaw with the remaining of four outstanding teeth and missing the lateral teeth on both sides of the lower jaw, so the treatment is essential to be establish. Results Complete oral rehabilitation of this case consisted in a upper removable denture and a lower hybrid prosthesis with precision attachment system, in order to achieve the aesthetic and functional aspects. Conclusions Using precision attachment system in hybrid prosthesis provide many advantages, but the fabricating this type of prosthesis require correct execution of clinical and technological steps, knowledge and silks both for the technician and specialist in prosthodontics. his is a model.